Vicky Cristina Barcelona - Aronson, Letty, 1943-; Tenenbaum, Stephen; Wiley, Gareth, 1962-; Allen, Woody, 1935-; Bardem, Javier, 1969-; Johansson, Scarlett, 1984-; Cruz, Penelope; Hall, Rebecca, 1982-; Clarkson, Patricia; Dunn, Kevin, 1956-; Messina, Chris (OSCAR : classic movies, 2008)
Two American women, one engaged to be married and the other sexually flirtatious, both become romantically involved with a painter while on vacation in Barcelona, only to find they have competition in the form of the painter's ex-wife.